THE UNIQUE PROFESSIONAL COMPETENCIES OF ENGLISH LANGUAGE TEACHERS (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article analyzes the unique professional competencies of English language teachers. Additionally, it discusses English teachers’ ability to adopt an individual approach to students, engage in reflective practice, and apply creative methods in the educational process. The research findings demonstrate the impact of these professional competencies on students’ learning effectiveness. This article serves as a valuable resource for English language teachers, educators, and researchers in the field of education.